Proceedings of the 48h IEEE Conference on Decision and Control (CDC) Held Jointly With 2009 28th Chinese Control Conference 2009
DOI: 10.1109/cdc.2009.5400575
|View full text |Cite
|
Sign up to set email alerts
|

Exponential stability region estimates for the State-Dependent Riccati Equation controllers

Abstract: Abstract-We investigate the nonlinear exponential stability of the State-Dependent Riccati Equation (SDRE)-based control. The SDRE technique is a nonlinear control method, which has emerged since the mid 1990's and has been applied to a wide range of nonlinear control problems. Despite the systematic method of SDRE, it is difficult to prove stability because the general analytic solution to the SDRE is not known. Some notable prior work has shown local asymptotic stability of SDRE by using numerical and analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Sontag [11] has shown that if a CLF is known for a nonlinear system that is affine in the control, then the CLF and the system equations can be used to find controllers that make the system asymptotically stable. Chang and Chung (2009) have recognized that SDRE stability usually only exists in a local region and at its best will be the ROA which is the expanded local region of stability. They have come up with a new strategy called contraction analysis to estimate the exponential stability region for the SDRE controlled system.…”
Section: Control Lyapunov Function (Clf) Based Approachmentioning
confidence: 99%
“…Sontag [11] has shown that if a CLF is known for a nonlinear system that is affine in the control, then the CLF and the system equations can be used to find controllers that make the system asymptotically stable. Chang and Chung (2009) have recognized that SDRE stability usually only exists in a local region and at its best will be the ROA which is the expanded local region of stability. They have come up with a new strategy called contraction analysis to estimate the exponential stability region for the SDRE controlled system.…”
Section: Control Lyapunov Function (Clf) Based Approachmentioning
confidence: 99%
“…28 Chang and Chung proposed a strategy based on contraction analysis to estimate the exponential stability region for SDRE controlled systems. 29 Furthermore, there are some review papers addressing the SDRE method. [30][31][32][33] For aerospace applications, most of spacecraft require position and attitude maneuver to complete space missions, such as rendezvousing, docking, debris removal, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Note that computing the state transition matrix for different values of t 0 corresponds to perturbing the system at different times along the perching trajectory. The figure shows that the longitudinal state transition matrix comprises of bounded elements for Φ(t, 0), Φ(t, 10) and Φ(t, 17) but becomes unbounded in the case of Φ(t, 25). Note that since this system possesses time-varying dynamics, therefore the behavior of the system in response to perturbations hitting the system at different times, can be different.…”
Section: Iiib Aircraft Dynamicsmentioning
confidence: 99%
“…This linearization is distinct from the state-dependent coefficient factorization wherein the nonlinear equations are represented as linear structures with state-dependent coefficients (See Chang and Chung 25 for an example). This thus forms the motivation for having the controller structure shown in Figure 5 -a variable (symmetric) dihedral trajectory is applied that keeps the aircraft reasonably close to (but not exactly on) the reference perching trajectory; the elevator and the twist are controlled in the feedback paths to keep the aircraft more closer to the perching trajectory as well as reject wind disturbances that may hit the aircraft.…”
mentioning
confidence: 99%